Efficient LCD screen assembling method based on nanometer materials

By using nanomaterials in the LCD screen assembly method and combining advanced preparation and assembly technology, the shortcomings of traditional LCD screens in terms of brightness, contrast, response time, power consumption and reliability are solved, and more efficient display performance and higher user satisfaction are achieved.

CN119916600AInactive Publication Date: 2025-05-02GUANGDONG WEISHI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411981649.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional LCD screens have room for improvement in brightness, contrast, response time, power consumption and long-term use reliability.

Method used

Using an efficient LCD screen assembly method based on nanomaterials, nano zinc oxide, nano indium tin oxide, nano silica and nano titanium dioxide are combined with chemical vapor deposition or solution method to prepare nanomaterials, and through spin coating and strict assembly and testing procedures, an efficient LCD screen is formed.

Benefits of technology

It significantly improves the display performance of LCD screens, including brightness, contrast and response time, while reducing power consumption and improving product reliability and user visual satisfaction.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an efficient LCD screen assembling method based on a nanometer material. According to the invention, the application of the nano material in the LCD screen assembling method brings the beneficial effect of remarkably improving the display performance. Firstly, due to the use of materials such as nano zinc oxide and nano indium tin oxide, excellent transparent conductive characteristics are provided for the LCD screen; due to the nanoscale effect of the materials, the materials can keep high transparency and have low surface resistance, so that the power consumption of a screen is reduced, and the electro-optical conversion efficiency is improved. The nano zinc oxide is used as a semiconductor material, and the crystal structure and the electronic property of the nano zinc oxide are optimized at the nanoscale, so that the LCD screen can more effectively block backlight when displaying black, and can more fully transmit light when displaying white, thereby improving the contrast ratio. Due to the addition of the nano silicon dioxide and the nano titanium dioxide, the surface flatness and the optical performance of the LCD screen are enhanced, so that the readability of the screen under various illumination conditions is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of LCD screen production, and in particular relates to a high-efficiency LCD screen assembly method based on nano materials. Background Art

[0002] With the continuous development of display technology, liquid crystal displays (LCDs) have become mainstream display products widely used in various electronic devices. However, traditional LCD screens still have certain limitations in display performance, power consumption and reliability. In order to meet the growing market demand, researchers are constantly exploring new technologies and materials to improve the performance of LCD screens. Existing LCD screen assembly methods mostly use traditional materials and technologies, which can meet display requirements to a certain extent, but there is still room for improvement in brightness, contrast, response time and other aspects.

[0003] However, traditional LCD screens also have certain shortcomings in terms of power consumption and long-term reliability. While maintaining high transparency, the surface resistance is high, which increases the power consumption of the screen and improves the electro-optical conversion efficiency. Summary of the invention

[0004] The purpose of the present invention is to provide a high-efficiency LCD screen assembly method based on nanomaterials in order to solve the above-mentioned problems.

[0005] The technical solution adopted by the present invention is as follows: a high-efficiency LCD screen assembly method based on nanomaterials, characterized in that the method comprises the following steps:

[0006] S1: First, prepare nanomaterials, weigh 80-100 parts by weight of nano zinc oxide, 15-20 parts by weight of nano indium tin oxide, 3-5 parts by weight of nano silicon dioxide, 2-4 parts by weight of nano titanium dioxide and 5-10 parts by weight of reinforcing compounding agent;

[0007] S2: Drying and grinding the raw materials for subsequent preparation process;

[0008] S3: preparing nanomaterials: mixing the raw materials according to the proportions in step S1, and preparing them by chemical vapor deposition or solution method;

[0009] S4: centrifuging, washing and drying the prepared nanomaterial to obtain pure nanomaterial;

[0010] S5: Select substrate material: Select glass or plastic with good light transmittance and heat resistance as the substrate material;

[0011] S6: Clean the surface of the substrate with deionized water and alcohol to ensure that the substrate is clean;

[0012] S7: placing the cleaned substrate into an oven to remove moisture; coating the substrate with a uniform nanomaterial layer by a spin coating method;

[0013] S8: placing the coated substrate into an oven for curing to fix the nanomaterial layer;

[0014] S9: Selecting liquid crystal material: Selecting liquid crystal material with excellent electro-optical properties; Mixing: Mixing the liquid crystal material and the nano material according to the proportion of step S1;

[0015] S10: stirring: stirring fully to make the liquid crystal material and the nano material uniformly mixed; filtering: filtering the mixed solution to remove impurities; vacuum degassing: placing the mixed solution in a vacuum container to remove bubbles;

[0016] S11: pre-assembly: pre-assemble the substrate and the driving circuit board; inject liquid crystal: inject the liquid crystal mixture between the substrates under vacuum conditions; seal: use ultraviolet light curing glue or heat sealing technology to seal the liquid crystal box; aging: put the sealed liquid crystal box into an aging box for aging treatment;

[0017] S12: Connect the electrodes of the liquid crystal box to the connectors on the driver circuit board to ensure that the electrical signals can be transmitted correctly; then assemble the liquid crystal box with the backlight source, and then assemble the liquid crystal display and other components into a complete LCD module; perform a final functional test on the assembled LCD module, including brightness, color, and response time; clean and anti-statically treat the LCD modules that have passed the test, and package them for shipment, after which the entire high-efficiency LCD screen assembly process based on nanomaterials can be completed.

[0018] In a preferred embodiment, in step S1, the reinforcing compound comprises: 1 part by weight of silver nanoparticles, 0.5 part by weight of a silane coupling agent and 0.5 part by weight of an organic silane.

[0019] In a preferred embodiment, in step S2, the mixed nanomaterials are placed in a vacuum drying oven and dried at 65° C. for 24 hours with the vacuum degree maintained at 0.1 Torr; the dried material is ground using an air abrasive polisher to further reduce the particle size and improve the dispersibility.

[0020] In a preferred embodiment, in step S3, the dried and ground nanomaterial is transferred to a solution process reactor, 100 ml of isopropanol and 2 g of polyvinyl pyrrolidone are added as dispersants; and the mixture is stirred in an ultrasonic cell disruptor at a power of 400 W and a frequency of 20 kHz for 1 hour.

[0021] In a preferred embodiment, in step S4, the nanomaterial suspension obtained by the solution method is placed in a centrifuge and centrifuged at a speed of 10,000 rpm for 30 minutes; the precipitate is washed 5 times with deionized water, centrifuged again after each washing, and finally vacuum dried at 50°C for 48 hours to obtain pure nanomaterial.

[0022] In a preferred embodiment, in step S5, float glass with a thickness of 0.7 mm is selected, with a light transmittance greater than 92% and a heat-resistant temperature greater than 300°C.

[0023] In a preferred embodiment, in step S6, an ultrasonic cleaner is used to clean the substrate in deionized water at 60° C. for 10 minutes, then in anhydrous ethanol at 70° C. for 10 minutes, and finally dried with nitrogen.

[0024] In a preferred embodiment, in step S7, the cleaned substrate is fixed on a spin coater and first rotated at a speed of 500 rpm for 20 seconds and then rotated at a speed of 3500 rpm for 40 seconds to form a uniform nanomaterial layer.

[0025] In a preferred embodiment, in step S8, the coated substrate is placed in an oven and the temperature is gradually increased from room temperature to 150°C at a rate of 2°C / min, and the temperature is maintained at 150°C for 60 minutes for curing.

[0026] In a preferred embodiment, in step S9, a twisted nematic liquid crystal material is selected, whose clearing point is 70°C, freezing point is -20°C, and response time is less than 5 milliseconds; during pre-assembly, a high-precision alignment machine is used to ensure that the alignment accuracy of the substrate and the driver circuit board is within ±20μm; under a vacuum degree of 0.3Torr, the liquid crystal mixture is injected between the substrates at a speed of 0.3ml / min; UV curing glue is used at 50mW / cm 2 The sealed liquid crystal box is placed in an aging box and aged at 55°C for 24 hours.

[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0028] 1. In the present invention, the application of nanomaterials in the LCD screen assembly method brings about the beneficial effect of significantly improving the display performance. First, the use of materials such as nano zinc oxide and nano indium tin oxide provides excellent transparent conductive properties for the LCD screen. The nanoscale effect of these materials enables them to have low surface resistance while maintaining high transparency, thereby reducing the power consumption of the screen and improving the electro-optical conversion efficiency. As a semiconductor material, the crystal structure and electronic properties of nano zinc oxide are optimized at the nanoscale, so that the LCD screen can block the backlight more effectively when displaying black, and can transmit light more fully when displaying white, thereby improving the contrast.

[0029] The addition of nano-silicon dioxide and nano-titanium dioxide enhances the surface flatness and optical properties of LCD screens. These materials can effectively scatter light, reduce glare and reflection, thereby improving the readability of the screen under various lighting conditions. At the same time, the high specific surface area and surface activity of nanomaterials enable them to form a more uniform and dense coating during the coating process, which helps to reduce light leakage between pixels and further improve display clarity. Therefore, the comprehensive application of these nanomaterials not only improves the brightness and color performance of LCD screens, but also enhances its viewing experience at different viewing angles, thereby greatly improving the user's visual satisfaction.

[0030] 2. In the present invention, strict quality control measures are adopted in each step of the entire assembly process, from the pre-assembly of the liquid crystal box to the final LCD module test. For example, the vacuum condition during the liquid crystal injection process ensures that there are no bubbles and impurities in the box, which helps to prevent display defects and performance degradation in long-term use. The choice of sealing technology prevents the leakage of liquid crystal and the intrusion of external contaminants, which are important factors in improving product reliability. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0032] Embodiment 1:

[0033] A high-efficiency LCD screen assembly method based on nanomaterials, the method comprising the following steps:

[0034] S1: First, prepare nanomaterials, weigh 80-100 parts by weight of nano zinc oxide, 15-20 parts by weight of nano indium tin oxide, 3-5 parts by weight of nano silicon dioxide, 2-4 parts by weight of nano titanium dioxide and 5-10 parts by weight of reinforcing compounding agent;

[0035] S2: Drying and grinding the raw materials for subsequent preparation process;

[0036] S3: preparing nanomaterials: mixing the raw materials according to the proportions in step S1, and preparing them by chemical vapor deposition (CVD) or solution method;

[0037] S4: centrifuging, washing and drying the prepared nanomaterial to obtain pure nanomaterial;

[0038] S5: Select substrate material: Select glass or plastic with good light transmittance and heat resistance as the substrate material;

[0039] S6: Clean the surface of the substrate with deionized water, alcohol, etc. to ensure that the substrate is clean;

[0040] S7: Put the cleaned substrate into an oven to remove moisture. Use a spin coating method to coat a uniform layer of nanomaterial on the substrate;

[0041] S8: placing the coated substrate into an oven for curing to fix the nanomaterial layer;

[0042] S9: Select liquid crystal material: Select liquid crystal material with excellent electro-optical properties. Mix: Mix the liquid crystal material and the nano material according to the proportion in step S1;

[0043] S10: Stirring: Stirring thoroughly to make the liquid crystal material and the nanomaterial evenly mixed. Filtering: Filtering the mixed solution to remove impurities. Vacuum degassing: Putting the mixed solution into a vacuum container to remove bubbles;

[0044] S11: Pre-assembly: pre-assemble the substrate and the driver circuit board. Injecting liquid crystal: injecting the liquid crystal mixture between the substrates under vacuum conditions. Sealing: using UV curing glue or heat sealing technology to seal the liquid crystal box. Aging: putting the sealed liquid crystal box into an aging box for aging treatment;

[0045] S12: Connect the electrodes of the liquid crystal box to the connectors on the driver circuit board to ensure that the electrical signals can be transmitted correctly. Then assemble the liquid crystal box with the backlight source, and then assemble the liquid crystal display and other components into a complete LCD module. Perform the final functional test on the assembled LCD module, including brightness, color, response time, etc. The LCD modules that have passed the test are cleaned, anti-statically treated, and packaged for shipment, and then the entire high-efficiency LCD screen assembly process based on nanomaterials is completed.

[0046] In step S1, the reinforcing compound comprises: 1 part by weight of silver nanoparticles, 0.5 part by weight of a silane coupling agent and 0.5 part by weight of an organic silane.

[0047] In step S2, the mixed nanomaterials are placed in a vacuum drying oven and dried at 65° C. for 24 hours with a vacuum degree maintained at 0.1 Torr. The dried materials are ground using an air abrasive polisher to further reduce the particle size and improve the dispersibility.

[0048] In step S3, the dried and ground nanomaterials were transferred to a solution process reactor, 100 ml of isopropanol and 2 g of polyvinylpyrrolidone (PVP) were added as dispersants, and stirred in an ultrasonic cell disruptor at a power of 400 W and a frequency of 20 kHz for 1 hour.

[0049] In step S4, the nanomaterial suspension obtained by the solution method is placed in a centrifuge and centrifuged at 10,000 rpm for 30 minutes. The precipitate is washed with deionized water for 5 times, centrifuged again after each washing, and finally vacuum dried at 50° C. for 48 hours to obtain pure nanomaterials.

[0050] In step S5, a float glass with a thickness of 0.7 mm is selected, with a light transmittance greater than 92% and a heat-resistant temperature greater than 300°C.

[0051] In step S6, the substrate is cleaned in deionized water at 60° C. for 10 minutes using an ultrasonic cleaner, then cleaned in anhydrous ethanol at 70° C. for 10 minutes, and finally dried with nitrogen.

[0052] In step S7, the cleaned substrate is fixed on a spin coater and first rotated at a speed of 500 rpm for 20 seconds and then at a speed of 3500 rpm for 40 seconds to form a uniform nanomaterial layer.

[0053] In step S8, the coated substrate is placed in an oven and the temperature is gradually increased from room temperature to 150°C at a rate of 2°C / min, and the temperature is maintained at 150°C for 60 minutes for curing.

[0054] In step S9, a twisted nematic (TN) liquid crystal material is selected, with a clearing point of 70°C, a freezing point of -20°C, and a response time of less than 5 milliseconds. During pre-assembly, a high-precision alignment machine is used to ensure that the alignment accuracy of the substrate and the driver circuit board is within ±20μm. Under a vacuum degree of 0.3Torr, the liquid crystal mixture is injected between the substrates at a rate of 0.3ml / min. A UV-cured adhesive is used at 50mW / cm 2 The sealed liquid crystal box was placed in an aging box and aged at 55°C for 24 hours.

[0055] Embodiment 2:

[0056] A high-efficiency LCD screen assembly method based on nanomaterials, the method comprising the following steps:

[0057] S1: First, prepare nanomaterials, weigh 80-100 parts by weight of nano zinc oxide, 15-20 parts by weight of nano indium tin oxide, 3-5 parts by weight of nano silicon dioxide, 2-4 parts by weight of nano titanium dioxide and 5-10 parts by weight of reinforcing compounding agent;

[0058] S2: Drying and grinding the raw materials for subsequent preparation process;

[0059] S3: preparing nanomaterials: mixing the raw materials according to the proportions in step S1, and preparing them by chemical vapor deposition (CVD) or solution method;

[0060] S4: centrifuging, washing and drying the prepared nanomaterial to obtain pure nanomaterial;

[0061] S5: Select substrate material: Select glass or plastic with good light transmittance and heat resistance as the substrate material;

[0062] S6: Clean the surface of the substrate with deionized water, alcohol, etc. to ensure that the substrate is clean;

[0063] S7: Put the cleaned substrate into an oven to remove moisture. Use a spin coating method to coat a uniform layer of nanomaterial on the substrate;

[0064] S8: placing the coated substrate into an oven for curing to fix the nanomaterial layer;

[0065] S9: Select liquid crystal material: Select liquid crystal material with excellent electro-optical properties. Mix: Mix the liquid crystal material and the nano material according to the proportion in step S1;

[0066] S10: Stirring: Stirring thoroughly to make the liquid crystal material and the nanomaterial evenly mixed. Filtering: Filtering the mixed solution to remove impurities. Vacuum degassing: Putting the mixed solution into a vacuum container to remove bubbles;

[0067] S11: Pre-assembly: pre-assemble the substrate and the driver circuit board. Injecting liquid crystal: injecting the liquid crystal mixture between the substrates under vacuum conditions. Sealing: using UV curing glue or heat sealing technology to seal the liquid crystal box. Aging: putting the sealed liquid crystal box into an aging box for aging treatment;

[0068] S12: Connect the electrodes of the liquid crystal box to the connectors on the driver circuit board to ensure that the electrical signals can be transmitted correctly. Then assemble the liquid crystal box with the backlight source, and then assemble the liquid crystal display and other components into a complete LCD module. Perform the final functional test on the assembled LCD module, including brightness, color, response time, etc. The LCD modules that have passed the test are cleaned, anti-statically treated, and packaged for shipment, and then the entire high-efficiency LCD screen assembly process based on nanomaterials is completed.

[0069] In step S1, the reinforcing compound comprises: 1 part by weight of silver nanoparticles, 0.5 part by weight of a silane coupling agent and 0.5 part by weight of an organic silane.

[0070] In step S2, the mixed nanomaterials are placed in a vacuum drying oven and dried at 65° C. for 24 hours with a vacuum degree maintained at 0.1 Torr. The dried materials are ground using an air abrasive polisher to further reduce the particle size and improve the dispersibility.

[0071] In step S3, the dried and ground nanomaterials were transferred to a solution process reactor, 100 ml of isopropanol and 2 g of polyvinylpyrrolidone (PVP) were added as dispersants, and stirred in an ultrasonic cell disruptor at a power of 400 W and a frequency of 20 kHz for 1 hour.

[0072] In step S4, the nanomaterial suspension obtained by the solution method is placed in a centrifuge and centrifuged at 10,000 rpm for 30 minutes. The precipitate is washed with deionized water for 5 times, centrifuged again after each washing, and finally vacuum dried at 50° C. for 48 hours to obtain pure nanomaterials.

[0073] In step S5, a float glass with a thickness of 0.7 mm is selected, with a light transmittance greater than 92% and a heat-resistant temperature greater than 300°C.

[0074] In step S6, the substrate is cleaned in deionized water at 60° C. for 10 minutes using an ultrasonic cleaner, then cleaned in anhydrous ethanol at 70° C. for 10 minutes, and finally dried with nitrogen.

[0075] In step S7, the cleaned substrate is fixed on a spin coater and first rotated at a speed of 500 rpm for 20 seconds and then at a speed of 3500 rpm for 40 seconds to form a uniform nanomaterial layer.

[0076] In step S8, the coated substrate is placed in an oven and the temperature is gradually increased from room temperature to 150°C at a rate of 2°C / min, and the temperature is maintained at 150°C for 60 minutes for curing.

[0077] In step S9, a twisted nematic (TN) liquid crystal material is selected, with a clearing point of 70°C, a freezing point of -20°C, and a response time of less than 5 milliseconds. During pre-assembly, a high-precision alignment machine is used to ensure that the alignment accuracy of the substrate and the driver circuit board is within ±20μm. Under a vacuum degree of 0.3Torr, the liquid crystal mixture is injected between the substrates at a rate of 0.3ml / min. A UV-cured adhesive is used at 50mW / cm 2 The sealed liquid crystal box was placed in an aging box and aged at 55°C for 24 hours.

[0078] From the above we can know:

[0079] In the present invention, the application of nano materials in the LCD screen assembly method brings about the beneficial effect of significantly improving the display performance. First, the use of materials such as nano zinc oxide and nano indium tin oxide provides excellent transparent conductive properties for the LCD screen. The nanoscale effect of these materials enables them to have low surface resistance while maintaining high transparency, thereby reducing the power consumption of the screen and improving the electro-optical conversion efficiency. Specifically, as a semiconductor material, the crystal structure and electronic properties of nano zinc oxide are optimized at the nanoscale, so that the LCD screen can block the backlight more effectively when displaying black, and can transmit light more fully when displaying white, thereby improving the contrast.

[0080] In addition, the addition of nano-silicon dioxide and nano-titanium dioxide enhances the surface flatness and optical properties of the LCD screen. These materials can effectively scatter light, reduce glare and reflection, thereby improving the readability of the screen under various lighting conditions. At the same time, the high specific surface area and surface activity of nanomaterials enable them to form a more uniform and dense coating during the coating process, which helps to reduce light leakage between pixels and further improve display clarity. Therefore, the comprehensive application of these nanomaterials not only improves the brightness and color performance of the LCD screen, but also enhances its viewing experience at different viewing angles, thereby greatly improving the user's visual satisfaction.

[0081] In the present invention, precise assembly and testing processes are key to ensuring the reliability of LCD modules, which is fully reflected in the above method. Throughout the assembly process, from the pre-assembly of the liquid crystal box to the final LCD module testing, strict quality control measures are adopted at each step. For example, the vacuum condition during the liquid crystal injection process ensures that there are no bubbles and impurities in the box, which helps prevent display defects and performance degradation in long-term use. The choice of sealing technology, such as UV curing glue or heat sealing, provides a strong and sealed edge to prevent the leakage of liquid crystal and the intrusion of external contaminants, which are important factors in improving product reliability.

[0082] In addition, the aging treatment step allows the LCD box to stabilize under specific environmental conditions, which not only helps to eliminate stress inside the material, but also helps to detect potential early failures. Through this process, it can be ensured that the LCD box will show higher stability in subsequent assembly and use. In the final assembly step, the precise assembly of components such as connectors, backlights and frames, as well as the standardized operation of screw fixing, all provide structural firmness and consistency for the LCD module. The strict implementation of functional tests, including brightness, color and response time tests, ensures that each LCD module can meet the predetermined performance standards, thereby reducing the return rate and repair rate of products in the market.

[0083] In summary, this precise assembly and testing process not only improves the initial quality of the LCD module, but also ensures the stability and durability of the product in long-term use, which has significant beneficial effects on improving brand reputation, reducing maintenance costs and enhancing user satisfaction.

[0084] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0085] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-efficiency LCD screen assembly method based on nanomaterials, characterized in that: The method comprises the following steps: S1: First, prepare nanomaterials, weigh 80-100 parts by weight of nano zinc oxide, 15-20 parts by weight of nano indium tin oxide, 3-5 parts by weight of nano silicon dioxide, 2-4 parts by weight of nano titanium dioxide and 5-10 parts by weight of reinforcing compounding agent; S2: Drying and grinding the raw materials for subsequent preparation process; S3: preparing nanomaterials: mixing the raw materials according to the proportions in step S1, and preparing them by chemical vapor deposition or solution method; S4: centrifuging, washing and drying the prepared nanomaterial to obtain pure nanomaterial; S5: Select substrate material: Select glass or plastic with good light transmittance and heat resistance as the substrate material; S6: Clean the surface of the substrate with deionized water and alcohol to ensure that the substrate is clean; S7: placing the cleaned substrate into an oven to remove moisture; coating the substrate with a uniform nanomaterial layer by a spin coating method; S8: placing the coated substrate into an oven for curing to fix the nanomaterial layer; S9: Selecting liquid crystal material: Selecting liquid crystal material with excellent electro-optical properties; Mixing: Mixing the liquid crystal material and the nano material according to the proportion of step S1; S10: stirring: stirring fully to make the liquid crystal material and the nano material uniformly mixed; filtering: filtering the mixed solution to remove impurities; vacuum degassing: placing the mixed solution in a vacuum container to remove bubbles; S11: pre-assembly: pre-assemble the substrate and the driving circuit board; inject liquid crystal: inject the liquid crystal mixture between the substrates under vacuum conditions; seal: use ultraviolet light curing glue or heat sealing technology to seal the liquid crystal box; aging: put the sealed liquid crystal box into an aging box for aging treatment; S12: Connect the electrodes of the liquid crystal box to the connectors on the driver circuit board to ensure that the electrical signals can be transmitted correctly; then assemble the liquid crystal box with the backlight source, and then assemble the liquid crystal display and other components into a complete LCD module; perform a final functional test on the assembled LCD module, including brightness, color, and response time; clean and anti-statically treat the LCD modules that have passed the test, and package them for shipment, after which the entire high-efficiency LCD screen assembly process based on nanomaterials can be completed.

2. A high-efficiency LCD screen assembly method based on nanomaterials as claimed in claim 1, characterized in that: In the step S1, the reinforcing compound comprises: 1 part by weight of silver nanoparticles, 0.5 part by weight of a silane coupling agent and 0.5 part by weight of an organic silane.

3. The high-efficiency LCD screen assembly method based on nanomaterials as claimed in claim 1, characterized in that: In step S2, the mixed nanomaterials are placed in a vacuum drying oven and dried at 65° C. for 24 hours with the vacuum degree maintained at 0.1 Torr; the dried materials are ground using an air abrasive polisher to further reduce the particle size and improve the dispersibility.

4. The high-efficiency LCD screen assembly method based on nanomaterials as claimed in claim 1, characterized in that: In the step S3, the dried and ground nanomaterials are transferred to a solution process reactor, 100 ml of isopropanol and 2 g of polyvinyl pyrrolidone are added as dispersants, and stirred in an ultrasonic cell disruptor at a power of 400 W and a frequency of 20 kHz for 1 hour.

5. The high-efficiency LCD screen assembly method based on nanomaterials as claimed in claim 1, characterized in that: In step S4, the nanomaterial suspension obtained by the solution method is placed in a centrifuge and centrifuged at a speed of 10,000 rpm for 30 minutes; the precipitate is washed 5 times with deionized water, and centrifuged again after each washing, and finally vacuum dried at 50° C. for 48 hours to obtain pure nanomaterial.

6. The high-efficiency LCD screen assembly method based on nanomaterials as claimed in claim 1, characterized in that: In the step S5, a float glass with a thickness of 0.7 mm is selected, with a light transmittance greater than 92% and a heat-resistant temperature greater than 300°C.

7. The high-efficiency LCD screen assembly method based on nanomaterials as claimed in claim 1, characterized in that: In step S6, the substrate is cleaned in deionized water at 60° C. for 10 minutes using an ultrasonic cleaner, then cleaned in anhydrous ethanol at 70° C. for 10 minutes, and finally dried with nitrogen.

8. The high-efficiency LCD screen assembly method based on nanomaterials as claimed in claim 1, characterized in that: In the step S7, the cleaned substrate is fixed on a spin coater and first rotated at a speed of 500 rpm for 20 seconds and then rotated at a speed of 3500 rpm for 40 seconds to form a uniform nanomaterial layer.

9. The high-efficiency LCD screen assembly method based on nanomaterials as claimed in claim 1, characterized in that: In the step S8, the coated substrate is placed in an oven and the temperature is gradually increased from room temperature to 150°C at a rate of 2°C / min, and the temperature is maintained at 150°C for 60 minutes for curing.

10. The high-efficiency LCD screen assembly method based on nanomaterials as claimed in claim 1, characterized in that: In the step S9, a twisted nematic liquid crystal material is selected, whose clearing point is 70°C, freezing point is -20°C, and response time is less than 5 milliseconds; during pre-assembly, a high-precision alignment machine is used to ensure that the alignment accuracy between the substrate and the driver circuit board is within ±20 μm; under the condition of a vacuum degree of 0.3 Torr, the liquid crystal mixture is injected between the substrates at a speed of 0.3 ml / min; and a UV curing glue is used at 50 mW / cm 2 The sealed liquid crystal box is placed in an aging box and aged at 55°C for 24 hours.